PENGARUH METODE PEMBAYARAN QRIS TERHADAP KEPUTUSAN PEMBELIAN PADA PARAGRAPH COFFEE AND EATERY - Alzura, Nazira; Dewi, Lies Anggi Puspita (UM. Bengkulu, 2025)
Technological advances in digital payment systems are increasingly influencing the way consumers make transactions. In the culinary sector, the implementation of digital payment methods is becoming increasingly important because it offers convenience, efficiency in the transaction process, and reduces the risks arising from the use of cash transactions. One of the widely adopted payment methods is the Quick Response Code Indonesian Standard (QRIS), which allows customers to transact easily by scanning a QR code. The purpose of this study was to examine how Paragraph Coffee and Eatery customers' purchasing decisions are influenced by the use of QRIS. A total of 95 respondents were given a questionnaire to fill out as part of a quantitative descriptive research methodology. With a regression coefficient value of 0.717 and a significance level of less than 0.001, the findings of the regression analysis indicate that QRIS significantly influences purchasing decisions. In addition, the results of the Pearson correlation test indicate a very strong relationship between variables with a correlation value of 0.868. Meanwhile, the determination test (R²) shows that 75.4% of the variation in purchasing decisions can be explained by the QRIS variable. Based on the results of this study, it can be concluded that the implementation of the QRIS payment method has a positive contribution to customer purchasing decisions. These findings have strategic implications for business actors in optimizing the use of digital payment systems to increase business competitiveness and customer satisfaction. Keywords: Digital Payment Method, QRIS, Purchasing Decisions